Peningkatan Kemampuan Literasi Budaya dan Berpikir Kritis Siswa Kelas V SD di Gugus PGRI Pangkatan Melalui Model Pembelajaran FIVES Berbasis Budaya Lokal - Elly Agustina; Sri Dewi Nirmala; Fery Muhammad Firdaus (Continuous Education: Journal of Science and Research, 2026)
This study aimed to analyze the improvement of cultural literacy and critical thinking skills of fifth-grade elementary school students in the PGRI Pangkatan cluster through the implementation of the FIVES learning model based on local culture. The study employed a quasi-experimental approach with a Nonequivalent Pretest–Posttest Control Group Design. The research subjects were fifth-grade students of SDN 08 Pangkatan as the experimental class and SDN 02 Pangkatan as the control class. Data were collected through a cultural literacy questionnaire and a critical thinking skills test administered during the pretest and posttest stages. Data analysis was conducted using descriptive and inferential statistics, including Hotelling’s T² MANOVA and the Independent Samples t-test. The results indicated that the improvement in cultural literacy and critical thinking skills of students in the experimental class was higher than that of the control class. These findings suggest that the implementation of the local culture-based FIVES model is effective in simultaneously enhancing both competencies.